Preparasi 125I-Nimotuzumab dan Uji Biodistribusi Pada Mencit Normal - WIDYASTUTI WIDYASTUTI; ADANG HARDI GUNAWAN; FITRI RAHMAWATI (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
Nimotuzumab labeled with gamma emitting radionuclide is a monoclonal antibody used to detect cancer that overexpress EGFR (epidermal growth factor receptor). Preparation, characterization and biodistribution study on normal mice of 125I nimotuzumab has been carried out. Labeling was carried out using iodogen as oxidator, variation in radioactivity of 125I and reaction time, followed by radiochemical purity test, stability test, biodistribution test on mice and clearance test on Wistar rats. Characterisation and radiochemical purity test were carried out using size exclusion HPLC and paper chromatography with 85% methanol as eluents. Stability on storage at 4°C was observed within 4 weeks. Biodistribution and clearance through urine and faeces was observed within 24 hours and 3 days post injection respectively. Optimal radiolabeling of nimotuzumab was obtained using 1 mCi of 125I in 20 minutes reaction time with radiochemical purity of 98,1% ± 1,2%, and upon storage at 4°C within 2 weeks decreased to 95,3% ± 0,9%. SE HPLC showed similar retention time of nimotuzumab before and after radiolabeling. Biodistribution showed high accumulation of radioactivity in kidneys, liver, spleen, and thyroid, among which the kidneys was the highest. Clearance at 24 and 72 hrs post injection showed faecal excretion of 8,8% ± 0,4% and 14,7% ± 1,1% respectively and renal excretion of 52,7% ± 2,9% and 82% ± 0,6%. respectively. From this experiments it can be concluded that nimotuzumab can be highly labeled with 125I with good stability, and excreted from the body mainly through kidneys.